Development of Adaptive E-Learning Content to Increase Learning Effectiveness - Solehuddin, Moh.; Sopandi, Encep; Saputra, Dedi Gunawan; Dhaniswara, Erwin; Yulianto, Sri; Wei, Zhang; Xu, Shanshan (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
The development of technology that is increasingly sophisticated and facilitates human work in all fields, is put to good use by people who understand the huge positive impact it has. The use of adaptive E-Learning content to enhance learning will have a major impact on Education. The adaptive E-Learning system was developed on the assumption that individual learning models are able to provide better results than other learning models. Therefore, the learning process in today's era can no longer be done traditionally, it must be able to adapt to the times. Educators must be able to balance it with methods that suit the needs of students. So that they can develop their potential and be able to have high self-esteem. As well as being able to be competitive and compete with many people of their age for creative content. The data obtained through the distribution of questionnaires. The questionnaire was made using the Google form with 15 statements about the effectiveness of E-Learning in learning. The results of this study explain that it is proven that the development of E-Learning content that is maximally adaptive according to existing procedures, can increase the effectiveness of learning by educators for students. This will realize that learning can be achieved in accordance with what has been set. The method used in this study is a quantitative method by collecting population and samples. The conclusion from this study is that the development of adaptive E-Learning content is proven to be implemented properly and efficiently to increase the effectiveness of learning in the classroom. The limitation of this research is that researchers only conduct this research at the elementary school level, which incidentally requires the use of adaptive E-Learning technology in the learning process, which is of course very beneficial for educators and students to improve the quality of education.